The effect of high and low percentage ball possession on physical and technical profiles in English FA Premier League soccer matches - Bradley, P. S.; Lago-Peñas, C.; Rey, E.; Gomez Diaz, A. (Journal of Sports Sciences, 2013)
The aim of this study was to examine the effects of high (HPBPT) and low percentage ball possession teams (LPBPT) on physical and technical profiles in elite soccer matches. Match performance data were collected from players in the English FA Premier League (n = 810) using a multiple-camera computerised tracking system. Physical indicators such as the total (10690 ± 996 vs 10778 ± 979 m; effect size [ES] = 0.11) and high-intensity running distance covered in matches (931 ± 299 vs 938 ± 311 m; ES = 0.13) did not differ between HPBPT and LPBPT. However, high-intensity running with ball possession in HPBPT was 31% higher (P < 0.01) than LPBPT (449 ± 266 vs 343 ± 236 m; ES = 0.42) but 22% lower without ball possession (423 ± 153 vs 539 ± 177 m; ES = 0.73). Players in HPBPT performed 44% more (P < 0.01) passes than those in LPBPT (35.3 ± 14.2 vs 24.6 ± 11.2; ES = 0.83). This trend was also evident (P < 0.05) for successful passes, received passes, touches per possession, shots, dribbles and final-third entries (ES range of 0.20-0.94). Central defenders of LPBPT covered 33% less (P < 0.01) high-intensity running with ball possession than central defenders of HPBPT. While fullbacks, attackers, central and wide midfielders of LPBPT covered more (P < 0.01) high-intensity running without and less with ball possession than their HPBPT counterparts (ES range of 0.91-1.23). Technical indicators such as total passes and passes received were higher (P < 0.01) across all positions in HPBPT than LPBPT (ES range of 0.82-1.52). The data demonstrate that percentage ball possession does not influence the overall activity profile of a team but impacts on the composition of high-intensity running efforts (with and without ball) and some technical elements of performance. Position-specific changes in physical and technical profiles were evident for teams employing different ball possession percentages and this information could aid training preparation.